The experience of change and psychological growth in people with psychotic symptoms: a phenomenological approach - Mapplebeck, Clare (2010)
Objective. The present study explored people‘s subjective experiences of positive change to understand if experiences of growth are evident in people who have experienced trauma and psychosis.